ECONOMIC EMPOWERMENT OF MUSTAHIK THROUGH OPTIMIZING PRODUCTIVE ZAKAT MANAGEMENT IN MOJOSARI VILLAGE, KAUMAN DISTRICT, TULUNGAGUNG REGENCY - sulistyawan, Arie; Deyisnil Fariadi (STAI Nusantara Kota Banda Aceh, 2025)
Productive zakat is a strategic instrument in the economic empowerment of the community that can transform mustahik into muzakki. This study aims to analyze the implementation and impact of the mustahik economic empowerment program through optimizing the management of productive zakat in Mojosari Village, Kauman District, Tulungagung Regency. The research method uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects included the administrators of amil zakat institutions, mustahik recipients of the program, and local community leaders. The results show that zakat management in Mojosari Village before the program was still traditional and consumptive with a low level of empowerment effectiveness. The implementation of the empowerment program through productive zakat was carried out with a participatory approach including stages of socialization, entrepreneurship training, distribution of business capital, and ongoing mentoring. This program succeeded in increasing the average income of mustahik by 45-60% within 6 months, increasing economic independence, and creating a multiplier effect on the village economy. Supporting factors for the program's success include the commitment of LAZ administrators, active participation of mustahik, and support from community leaders. Meanwhile, the challenges faced include limited human resources for management, fluctuations in the businesses of mustahiq recipients, and the need for increased awareness among muzakki (zakat payers). This study recommends strengthening the institutional capacity of LAZ (Islamic Zakat Institutions), diversifying productive businesses, and developing a more systematic monitoring and evaluation system for the sustainability of the mustahiq economic empowerment program through productive zakat.